The conflict between the obligation of the effective servant to the college of appointment of the contracted servant as contracting agent in bidding procedures: an analysis of legality between art. 7th, I, and art. 8th, caput, of Law no. 14,133/21 - Silva, Paulo Antônio da; Ventura, Luciana (JRG Journal of Academic Studies, 2024)
This article deals with the antinomy between art. 7, I, and art. 8, caput, of Law 14.133/21, regarding the issue of contracted versus permanent civil servants in the bidding procedure. This discussion has led legal practitioners to question the availability of applying both rules to the same fact, even in the face of the extension of time prescribed in art. 176, which will expire on March 31, 2027, the date on which it becomes fully effective. The study was carried out by applying conclusive, deductive research methodology through exploratory, bibliographic and documentary immersion with qualitative and quantitative procedures. This approach considers the ineffectiveness of the legislation due to the conflict between the articles mentioned. In view of these facts, the following specific objectives emerged to be studied in this work: to analyze articles 7, I, and 8 caput of Law 14.133/21, in terms of their characteristics, applicability and differences; to present the different forms of investiture in public power; to investigate how the number of civil servants available in the bodies can influence the applicability of the rule; verify the possibility of bidding processes being null and void if the contracting agent is not a permanent civil servant; present the jurisprudential and doctrinal understanding of the applicability of the rules. In this context, it emerges that it is possible to appoint non-permanent civil servants, provided there is justification, when the body does not have the necessary professional on its staff. This result is obtained through case law, doctrine and regulations, which grant autonomy to the manager. Furthermore, if this understanding persists in some supervisory bodies, it is preferable to maintain the provisions of the law in its entirety.